1993
DOI: 10.1038/366156a0
|View full text |Cite
|
Sign up to set email alerts
|

Different types of calcium channels mediate central synaptic transmission

Abstract: Synaptic transmission is mediated by calcium entry through voltage-dependent calcium channels in presynaptic nerve terminals. Various types of calcium channel have been characterized in neuronal somata, but it is not clear which subtypes induce transmitter release at central synapses. The N-type Ca2+ channel blocker omega-conotoxin GVIA (omega-CgTx) suppresses the excitatory postsynaptic responses only partially, whereas potassium-induced release of glutamate from brain synaptosomes can be blocked by omega-Aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
414
6
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(449 citation statements)
references
References 22 publications
24
414
6
5
Order By: Relevance
“…nels is known to be required for release of transmitter from hippocampal synapses (Takahashi and Momiyama 1993;Wheeler et al 1994). To test the hypothesis that cannabinoids mediate their effects on transmission in the hippocampus by inhibiting N-and P/Q-type calcium channels, the effects of cannabinoid receptor activation were measured before and after pharmacological blockade of these channels (Sullivan 1999).…”
Section: Cannabinoid-mediated Impairments Of Memorymentioning
confidence: 99%
“…nels is known to be required for release of transmitter from hippocampal synapses (Takahashi and Momiyama 1993;Wheeler et al 1994). To test the hypothesis that cannabinoids mediate their effects on transmission in the hippocampus by inhibiting N-and P/Q-type calcium channels, the effects of cannabinoid receptor activation were measured before and after pharmacological blockade of these channels (Sullivan 1999).…”
Section: Cannabinoid-mediated Impairments Of Memorymentioning
confidence: 99%
“…These genes encode large pore-forming proteins (Ͼ2200 amino acids) that are differentially distributed throughout the nervous system (Westenbroek et al, 1990(Westenbroek et al, , 1998. Synaptic N-, P/Q-, and R-type channels, formed by ␣ 1B , ␣ 1A , and ␣ 1E subunits, respectively, play a principal role in regulating neurotransmitter release (Turner et al, 1992;Takahashi and Momiyama, 1993;Wheeler et al, 1994;Wu et al, 1999).Ca 2ϩ channel ␤ subunits (subtypes 1-4) are highly homologous intracellular proteins with primary sequences ranging from 480 to 630 amino acids (for review, see Birnbaumer et al, 1998). The sequence can be divided into five domains on the basis of the regions of amino acid identity between subtypes.…”
mentioning
confidence: 99%
“…The observed effect of nimodipine and flunarizine on immune parameters could be due to their increased selectivity for the CNS (34,35). The L-, N-and P/Q-type calcium channels reportedly play a pivotal role in mediating calcium influx that triggers depolarization evoked neurotransmitter release in nerve terminals (12,13). It has been shown that neuronal communication of lymphoid tissue is possible and this may be an important route which allows functional interaction between the CNS and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory neurons have been shown to possess 5 distinct types of voltage dependent Ca 2~ channels designated as L, N, T, P and Q. The L, Nand P/Q-type Ca 2. channels have been implicated to play .an important role in mediating Ca 2 § influx that triggers depolarization evoked neurotransmitter release from nerve terminals (12,13). Calcium channel blockers (CCBs) are the agents which block the entry of Ca 2. into the cell by interacting with voltage-dependent Ca 2. channels.…”
Section: Introductionmentioning
confidence: 99%